Modified FCI (Fédération Cynologique Internationale) Scoring of the Coxofemoral Joint in Labrador Retrievers Without and With Hip Dysplasia - Mostafa, Ayman A.; Nahla, Menna A.; Ali, Khaled M.; Berry, Clifford R. (Frontiers in Veterinary Science, 2022)
The objective is to propose a modified FCI scoring protocol of the canine hip joint via: (1) providing morphometric criteria of each score; (2) quantifying the extent of lateral and dorsal acetabular femoral head (AFH) coverage; (3) evaluating the steepness of cranial acetabular edge (acetabular index angle) and inclination angle (IA) in normal and dysplastic coxofemoral joints of Labrador Retrievers. The long-term goal is to achieve a selective breeding protocol using parental phenotypically healthy coxofemoral joints based on the standard extended-leg VD radiograph to help reduce the prevalence of CHD among offspring. Investigated populations were classified into normal (grade A) and dysplastic coxofemoral joints (grades B to E) based on the morphometric criteria previously established by the conventional FCI scoring system. Center-edge (CE) angle, Norberg angle (NA), indices of dorsal AFH coverage width and area, acetabular index angle, and inclination angle were determined for each group. Variables were compared between groups using ANOVA. Spearman correlation coefficient was used to determine the linear relationship between selected variables. Overall, all radiographic measurements differed significantly (P < 0.0001) among the five tested groups using ANOVA test. Dorsal AFH coverage area index was the only measure that differed significantly (P ≤ 0.007) between every two consecutive groups using Tukey's test. Significant correlations were identified between the Norberg and CE angles (rs = 0.95, P < 0.0001), the width and area of dorsal AFH coverage (rs = 0.96, P < 0.0001), and the radiographic techniques utilized to assess lateral vs. dorsal AFH coverage (rs ≥ 0.80, P < 0.0001). Evaluation of CE-angle, dorsal AFH coverage area index and acetabular index angle is recommended during selective breeding to include parents with radiographically healthy joints and reduce the incidence of hip dysplasia among offspring. Dogs with CE-angle <27°, dorsal AFH coverage area index <53%, and/or acetabular index angle >9° may be consistent with hip dysplasia and are recommended to be excluded from potential breeding groups. Re-evaluation of coxofemoral joints with borderline values located between near-normal and mildly dysplastic coxofemoral joints is strongly recommended to be performed after 6 months.